APPLICATION OF THE MONTE CARLO METHOD IN PREDICTING THE NUMBER OF BUDGET PROPOSALS ACCEPTED IN NORTH SUMATRA PROVINCIAL HEALTH OFFICE - Harahap, Riska; Siahaan, Maharani Putri Adam; Widyasari, Rina (Pena Cendekia Insani, 2024)
A budget is a planning tool regarding future expenditure and revenues, generally prepared for one year. The prediction simulation for approved budget proposals is an estimate of the calculation of the approval rate for approved proposals in the following year. This research uses the Monte Carlo method in solving problems. This method can be used in problems with nonlinear boundary conditions, namely prediction limits.the author uses a quantitative descriptive method, which is a form of research that focuses on the facts and characteristics of the research object by combining related variables. This research uses the Monte Carlo method uses random numbers and probability statistics to solve problems.The data used to predict the approved proposal budget is the budget proposal data that is approved each year. The following is one of the approved proposal data, namely the approved budget proposal data from 2021, 2022 and 2023 budget proposals received using the Monte Carlo Method which has been implemented at the North Sumatra Provincial Health Service with the simulation namely with an average percentage in 2022 of 84% and in 2023 by 76%. So with the successful application of the Monte Carlo Method to predict the number of budget proposals received at the North Sumatra Provincial Health Service for 2024 it will provide convenience for the North Sumatra Provincial Health Service to find out what the predicted number of budget .